(untitled) (Scientific journal of the Fergana State University, 2024)
Rapid growth of the population leads to further complexity of problems such as effective use of labor resources, increase of employment of the population and improvement of the lifestyle of the population. In order to eliminate these problems, effective use of the natural, economic-social geographical and demographic potential of the regions, territorial planning of economic sectors is important. In the Development Strategy of New Uzbekistan for 2022-2026, «In the proportional development of the regions, important tasks for increasing the regional economy by 1.4 - 1.6 times have been defined [2]. In this regard, scientific researches aimed at territorial planning of economic sectors, taking into account the existing demographic potential of the regions and the possibilities of labor resources, are of great importance. The purpose of this research is to develop scientifically based conclusions on the territorial location of labor resources and employment in economic sectors in Andijan region, as well as regional planning of the economy. Geographical comparison, system-content, regional analysis, historical, statistical-mathematical and other methods were used in the article. In the conducted research work, the employment of labor resources of Andijan region in economic sectors and its changes, its territorial differences were analyzed. Important conclusions, suggestions and recommendations have been developed regarding the implemented analyzes. From the main conclusions and recommendations obtained in the research, Andijan region is of great importance as it serves to reduce regional differences in the planning and development of population employment and economic sectors, as well as to develop programs for improving the territorial structure.